PENERAPAN METODE PROCESS COSTING SYSTEM DALAM PENENTUAN HARGA POKOK PRODUKSI PADA PT. CONBLOC INDONESIA SURYA - Wensen, Christian Ray; Manossoh, Hendrik; Pinatik, Sherly (Universitas Sam Ratulangi, 2016)
Process costing is a system of pricing of basic products used in industrial production that organizes activities for a specific product based on an ongoing basis without specific demands from certain customers. Basic principles of process costing that accrue costs of operations or a specific department for one full period (monthly, quarterly, annually) and then dividing by the number of units produced during the period. This study aimed to quantify the cost of production by using the method of process costing at PT. Conbloc Indonesia Surya. Methods of data analysis used this research is descriptive qualitative research method,Â where the study was conducted by collecting data company, and analyze the collected data and provide particulars faced. Authors collected data were interviews and documentation. Based on the results of the study showed that the cost allocation made by PT. Conbloc Indonesia Surya yet remained, should the cost of water input into the cost of raw materials instead of factory overhead costs. Keywords: process costing, cost, cost of goods sold